Shaking table test study on the influence of environment vibration on the ancient city wall of Xi’an - Ruijuan Yang; Junlian Li; Masyitah Md Nujid (Case Studies in Construction Materials)
With the expansion of urban construction, more earthen sites are continuously damaged by environmental vibrations. The ancient city wall of Xi'an, which has a history of more than 600 years, is being affected by vibrations from subways, cars, and construction, yet the influence mechanism remains unclear. This research aims to elucidate the response discipline of Xi'an City Wall to environmental vibration effect through on-site monitoring and scaled model experiments. A 1:30 scale earthen wall model was subjected to 100 cycles of fixed-frequency and sweep-frequency vibrations. Crack width, vibration acceleration, and displacement were measured using fiber Bragg grating sensors, accelerometers, dynamic displacement meters, and high-speed cameras. The test results show that the response frequency of the earthen ruins was from 6 to 20 Hz. The peak acceleration and displacement of the city wall have a significant amplification effect as the height increases. The larger the initial width of the crack, the more significant the response to vibration will be. The findings presented in this study elucidate several critical characteristics related to the deterioration of the Xi'an City Wall. These insights are of considerable significance for the implementation of vibration isolation protection measures and the restoration efforts for this historical structure.